Pengukuran Nilai Grounding Terbaik Pada Kondisi Tanah Berbeda - Arifin, Jaenal (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2021)
A good grounding or grounding system is a mechanism to protect electronic devices. This protection can be direct or indirect during lightning strikes in rainy seasons. The characteristic and condition of the soil is one of the factors that can affect the grounding value. In this research, the measurement of grounding value is conducted in different soil conditions. The conditions are the watery, clay, dry, rocky, sand and swamp soils. This research purpose is to determine the value of grounding or grounding resistance in different type of soils. The measurement methods use three point method and four electrode method by sticking the electrodes into the ground. The value of the grounding resistance displayed on the measuring instrument (Earth Resistance Tester) would be smaller if the electrodes are planted deeper with the addition of electrode rods, and the distance between the electrodes is set between 5 to 10 meters.